Polydispersity of a mammalian chaperone: mass spectrometry reveals the population of oligomers in alphaB-crystallin. - Aquilina, J; Benesch, J; Bateman, O; Slingsby, C; Robinson, C (2003)
The quaternary structure of the polydisperse mammalian chaperone alphaB-crystallin, a member of the small heat-shock protein family, has been investigated by using electrospray mass spectrometry. The intact assemblies give rise to mass spectra that are complicated by the overlapping of charge states from the different constituent oligomers. Therefore, to determine which oligomers are formed by this protein, tandem mass spectrometry experiments were performed. The spectra reveal a distribution, primarily of oligomers containing 24-33 subunits, the relative populations of which were quantified, to reveal a dominant species being composed of 28 subunits. Additionally, low levels of oligomers as small as 10-mers and as large as 40-mers were observed. Interpretation of the tandem mass spectral data was confirmed by simulating and summing spectra arising from the major individual oligomers. The ability of mass spectrometry to quantify the relative populations of particular oligomeric states also revealed that, contrary to the dimeric associations observed in other small heat-shock proteins, there is no evidence for any stable substructures of bovine alphaB-crystallin isolated from the lens.